1970
DOI: 10.1103/physrevlett.25.1266
|View full text |Cite
|
Sign up to set email alerts
|

Electron Cyclotron Drift Instability

Abstract: out separately, by means of an axially and radially movable probe. We found, by interferometry, that the wave signals were primarily concentrated within the axial length of the T probes or grids. When the detecting probe was outside of this region, the signal dropped by 60 dB. Our measurements indicated that in the axial direction the waves were essentially standing waves, with the dominant Fourier components having twice the probe lengths; i.e., k^ir/l', etc. Thus, by approximating the standing waves in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(70 citation statements)
references
References 6 publications
1
69
0
Order By: Relevance
“…Forslund et al (1970), Gary (1971), and references in the review by Wu et al (1984)). It is a variety in the sense that the instability is not driven by the whole ions drifting as a bulk, yet just by an ion beam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forslund et al (1970), Gary (1971), and references in the review by Wu et al (1984)). It is a variety in the sense that the instability is not driven by the whole ions drifting as a bulk, yet just by an ion beam.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that it is a variety of the electron cyclotron drift instability, which was studied in the 70's and has since been all but forgotten (e.g. Forslund et al, 1970). The idea is illustrated in Figure 6a which displays the two ion beam modes at ω = k(V d ± v ti ) intersecting with the first three branches of Bernstein modes.…”
Section: Dispersion Analysismentioning
confidence: 99%
“…The relative bulk velocity between electrons and ions (which is proportional to u x1 /v te1 ) controls the type of microinstabilities, while the ratio of the plasma-tocyclotron frequency (ω pe /ω ce ) determines the dispersion relation of plasma waves. When the relative bulk velocity between electrons and ions exceeds the electron thermal velocity, electrostatic waves are excited by current-driven instabilities such as the Buneman-type instability (BI) 7 or the electron cyclotron drift instability (ECDI) 8,9 . At high-Mach-number perpendicular shocks, the relative velocity between incoming electrons and reflected ions commonly becomes much faster than the electron thermal velocity.…”
Section: Introductionmentioning
confidence: 99%
“…ECDI-driven waves are important for shock physics because they are capable of resonantly interacting with the bulk of the ion distribution and preferentially heating the electrons perpendicular to B o [Forslund et al, 1970[Forslund et al, , 1972Lampe et al, 1972]. More recent work has shown that the ECDI can produce a suprathermal tail on the ion distribution and can strongly heat the electrons [Muschietti and Lembège, 2013].…”
Section: A1 Themis Examplesmentioning
confidence: 99%